The Impact of Effective Teaching Strategies in a Variety of Physical Variables and Some Basic Skills for Students in Volleyball - Thuraya Jwaid Mohin (Journal of Global Pharma Technology, 2018)
The common method of teaching the various skills in general and the ball in particular is the American method, which requires the teacher to be a decision maker to the student and not a slander of us on this method and reduce its advantages, but the present era is the era of knowledge and educational development should be accompanied by this Evolution Previous studies have confirmed that there are many teaching methods that are unique in each of the objectives and characteristics and have an effective role in correcting mistakes and investing time and velocity in the process of learning, but these methods meet neglect of most workers in the teaching of physical education, As well as that there are limited possibilities in the performance of sports and linking them to the basic skills of the game volleyball. So the researcher looked at this problem by introducing effective teaching with different strategies in some physical variables and the basic skills of students in the volleyball and output outputs and effective results of the educational process.Preparing educational units using effective teaching in a variety of strategies (technical, cooperative and differentiated learning) in some physical variables and basic skills of students in volleyball.Learn about the effect of using effective teaching in a variety of strategies in some physical variables and basic skills of students in volleyball.Identify which strategies are more influential in some physical variables and basic skills of students with volleyball.The researcher used the experimental method and identified the research community with the students of the second stage in the Faculty of Physical Education and Sports Sciences at the University of Babylon for the academic year 2016 - 2017, the total number of (95) students, consisting of four divisions where the random method was adopted in the selection of the sample (80) (A) The first experimental group, the second experimental group (B), the third experimental group (D), and the control group (C). The most important conclusions are:The results showed the effectiveness of effective teaching in the strategy of technical learning in the learning and development of physical variables (the strength characteristic of the velocity of the arms, the strength characteristic of the velocity of the legs, the velocity of transition).The results showed the effectiveness of effective teaching in the strategy of cooperative learning in learning and improving the physical ability of explosive power.The results showed the effectiveness of effective teaching with a different learning strategy in learning and developing physical variables in the third degree.Keywords: Teaching strategies, Physical variables and volleyball.